Adaptive fan control - Blasinski, Petr; Rubina, Aleš; Rubinová, Olga; Jůza, Štěpán (IOP Pulishing, 2021)
The paper presents the possibility of management the fan performance in dependence on CO2 concentration. A mathematical calculation is made from the prediction of the electric energy consumption for a variant control algorithm. The most advantageous algorithm is programmed into the actual fan control system, and its power consumption is shown in graph. Finally, the saving of the adaptive control is compared to the classical control over time. To program the control algorithm, the CO2 mass balance equation is used. The equation depends on the input values, namely the number of CO2 sources, the room volume and the supply air. Due to the infinitely variable of fan control, it is possible to adjust the power setting depending on the expected development of the logarithmic rise of CO2 concentration in the room. This prediction is programmed with the Visual Basic code and program code can be used to the Arduino control unit, which controls the EC fan power with a 0-10 V signal. Although significant savings over a short period of time can not be expected, the ventilation system where the fan runs for a significant part of the year will be substantial. Therefore, the result will be presented by graphical diagrams of different ways of controlling the fan per year of operation.

The paper presents the possibility of management the fan performance in dependence on CO2 concentration. A mathematical calculation is made from the prediction of the electric energy consumption for a variant control algorithm. The most advantageous algorithm is programmed into the actual fan control system, and its power consumption is shown in graph. Finally, the saving of the adaptive control is compared to the classical control over time. To program the control algorithm, the CO2 mass balance equation is used. The equation depends on the input values, namely the number of CO2 sources, the room volume and the supply air. Due to the infinitely variable of fan control, it is possible to adjust the power setting depending on the expected development of the logarithmic rise of CO2 concentration in the room. This prediction is programmed with the Visual Basic code and program code can be used to the Arduino control unit, which controls the EC fan power with a 0-10 V signal. Although significant savings over a short period of time can not be expected, the ventilation system where the fan runs for a significant part of the year will be substantial. Therefore, the result will be presented by graphical diagrams of different ways of controlling the fan per year of operation.
Adaptive fan control
Keywords: air conditioning; fan control; CO2 concentration; air conditioning; fan control; CO2 concentration